PENGARUH FAKE BUYER DAN FAKE REVIEW TERHADAP PURCHASE INTENTION PRODUK FASHION PADA MARKETPLACE SHOPEE DENGAN TRUST SEBAGAI VARIABEL INTERVENING - Fauziya, Rafida Aviola Hana; Isa, Muzakar (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the effect of fake buyers and fake reviews with trust as a mediating variable on purchase intention. This study employs a quantitative research approach, drawing on a sample of 105 sellers from the Shopee marketplace. Data collection was conducted through the distribution of online questionnaires via Google Forms, with each question item evaluated using a Likert scale. For data analysis, the Partial Least Squares (PLS) method was utilized, and processed through the SmartPLS 4 software. The findings reveal that both fake buyers and fake reviews exert a positive impact on consumer trust. Furthermore, fake buyers and consumer trust influence purchase intention, whereas fake reviews do not directly affect purchase intention. However, trust plays a mediating role in the relationship between fake buyers and fake reviews with purchase intention. These results underscore the pivotal role of trust as a mediator in the dynamics between fake buyers, fake reviews, and purchase intention. Sellers should not only rely on short-term tactics such as fake buyers and fake reviews but also implement sustainable and ethical marketing strategies to build long-term consumer trust and loyalty. Keywords: Fake Buyer; Fake Review; Purchase Intention; Trust